Citation Cartels: Understanding Their Emergence and Impact on the Academic World - Willie, Michael Mncedisi (Manunggal Halim Jaya, 2024)
Citation metrics have become pivotal in evaluating academic research and influencing funding, promotions, and institutional prestige. However, the increasing emphasis on these metrics has given rise to unethical practices, notably citation cartels, which artificially inflate citation counts through collusive agreements among researchers or journals. This study investigates the prevalence and impact of citation cartels by analysing citation patterns in recent papers. Using a systematic approach, we examined citation data across five papers to identify patterns of collusion and the extent of citation inflation. The results reveal that Author 1 was cited in every reference across four out of five papers, either as a sole author or co-author, with a direct or indirect responsibility for 100% of the citations. Similarly, Authors 2 and 3 demonstrated substantial influence, with median citation shares of 36% and 35%, respectively. These findings highlight the significant role of key authors in shaping citation distributions and raise concerns about the integrity of citation metrics. The study concludes with recommendations for addressing citation cartels, including implementing detection systems, enhanced peer review processes, and a more balanced approach to evaluating research impact.